2021
DOI: 10.3390/foods10081866
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-Free Milk Chocolate as a Carrier of Omega-3 Polyunsaturated Fatty Acids and Probiotics: A Potential Functional Food for the Diabetic Population

Abstract: Chocolate is an adequate matrix to deliver bioactive ingredients. However, it contains high sugar levels, one of the leading causes of chronic degenerative diseases. This work aimed to evaluate the effects of milk chocolate reformulation with alternative sugar sweeteners (Sw; isomalt + stevia), probiotics (Prob), and ω-3 polyunsaturated fatty acids (PUFAs) on its physicochemical properties and consumers’ acceptability. Lactobacillus plantarum 299v (L. p299v) and Lactobacillus acidophilus La3 (DSMZ 17742) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…One of the benefits of using chocolate as carrier for the delivery of bioactive compounds is that it can mask unpleasant flavors. Therefore, bioactive ingredient such as ω-3 PUFAs, probiotics, phenolic extracts, vitamins, and minerals have been successfully added to chocolate formulations [9,[11][12][13][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Likewise, chocolate is also used as an ingredient for different food formulations, thus functional chocolates could also be used to fortify different foods.…”
Section: Chocolate As Carrier For the Delivery Of Bioactive Ingredientsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the benefits of using chocolate as carrier for the delivery of bioactive compounds is that it can mask unpleasant flavors. Therefore, bioactive ingredient such as ω-3 PUFAs, probiotics, phenolic extracts, vitamins, and minerals have been successfully added to chocolate formulations [9,[11][12][13][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Likewise, chocolate is also used as an ingredient for different food formulations, thus functional chocolates could also be used to fortify different foods.…”
Section: Chocolate As Carrier For the Delivery Of Bioactive Ingredientsmentioning
confidence: 99%
“…Similarly, a sugar-free milk chocolate formulation added with microencapsulated probiotics and fish oil rich in EPA/DHA was developed, using isomalt and stevia as sugar replacers (Table 2) [32]. The authors observed that the sugar-free milk chocolate matrix added with probiotic and fish oil was capable to maintain probiotic viability (>2 × 10 7 CFU per portion of 12 g) as well as the concentration of PUFAs (>130 mg per portion of 12 g) [32]. On the other hand, other authors [16] developed a sugar-free dark chocolate functional formulation, using erythritol, stevia, and isomalt as sugar replacers and extracts from beetroot, jamun seed, and pink pitahaya as bioactive ingredients, as well as coffee to mask the aftertaste.…”
Section: Darkmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, bacteria of genus Lactobacillus are used for the preparation of novel functional foods, their presence in the gastrointestinal tract being considered beneficial ( 2 ). Several studies indicated that these bacteria may contribute to the balance of the intestinal microbiota of the host and increase immunity, have antimicrobial effect against pathogenic bacteria, antiviral effects, are resistant to a wide range of pH and temperature, and are also thought to optimize digestion and milk tolerance ( 3 ). In addition, these microorganisms, known as probiotics, are active ingredients to improve the health of diabetic and non-diabetic consumers ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another novel and unconventional approach to food supplements was outlined by Gómez-Fernández et al [ 12 ]. In their paper, the authors evaluated the effects on consumers’ acceptability of a milk chocolate reformulation with alternative sugar sweeteners, probiotics, and ω-3 polyunsaturated fatty acids using milk chocolate as a carrier.…”
mentioning
confidence: 99%